The Role of Human Endothelial Cells in the Brain Tumour Organoid (BTO) Platform as a Unique Tool in Discovery of Novel Treatment Approaches in Glioblastoma. (16th November 2020) - Lubanska, Dorota; Soliman, Mohamed A.R; Shamisa, Abdalla; DeCarvalho, Ana; Rodzinka, Alex; Nyayachavadi, Adit; Rondeau-Gagné, Simon; Kulkarni, Swati; Porter, Lisa
Abstract: INTRODUCTION: Despite significant advancements in the understanding of brain tumor biology, the successful management of Glioblastoma multiforme (GBM) remains unclear. The required high success rate in the clinical practice depends on the progress in patient-tailored approaches. METHODS: A high-throughput BTO platform was developed, where individual nine GBM patient-derived low-propagated cell lines were grown and customized as mini-tumors. We optimized the microenvironment of the organoid by incorporating human endothelial cells (HUVECs) to better mimic that of the tumor in-vivo. We characterized the gene expression of the cultures separated via Fluorescence-activated cell sorting (FACS) and histopathology of organoids in comparison to the patient's neurosphere cultures. We tested the response of the generated BTO and co-cultured neurospheres to therapeutics used in the clinical practice compared to vehicle control. RESULTS: We found that BTOs with endothelial components exhibit more aggressive features including proliferation and invasiveness. We found significant upregulation of poor prognosis markers including YKL-40, MDR-1, FLT-1, and PCNA expression in the co-culture of patient cells with increasing number of endothelial cells. There was a significant increase in the better prognosis markers (DLL-3) with low number of endothelial cells in the culture. Incorporation of HUVECs significantly increased YKL-40 expression in all mesenchymal subtype patients. Patients' cells co-cultured with HUVECs in the BTO system demonstrated a significant increase in resistance to novel therapies (dacomitinib and vorinostat) in comparison to cultured neurospheres. CONCLUSION: This optimized BTO platform can potentially enable us to test a large number of drugs alone, and in combination, to stratify the best treatment regimens in a patient-tailored manner. Also, our model will answer several questions related to the role of the endothelial component in the GBM microenvironment to aid future discovery of new therapeutics.